TRANSLATION ACCURACY AND READABILITY OF IMPERATIVE SENTENCES IN SPENCER (2021) ON KLIKFILM - Septian Saputra; Eky Edel; Tantri Sari Safitry (LLDIKTI Wilayah X, 2024)
Streaming services, both local and international providers, have gained more interest over the last five years. In Indonesia, this phenomenon is seen in local streaming services such as KlikFilm, which offers thousands of unreleased movies in Indonesian theatres or major streaming services. Pablo Larrain's Spencer (2021) is one of the unreleased movies in Indonesian theatres and major streaming services, making KlikFilm the only local streaming service with the Indonesian subtitle of this movie. This qualitative descriptive study aims to discuss the types of imperative sentences, the translation techniques, and the quality of imperative sentence translation from the accuracy and readability aspects in the KlikFilm subtitle of Spencer. The writer uses content analysis and Focus Group Discussion (FGD) as the data collection technique. Following the theory of Swan (2016), 149 data are classified into five types of imperative sentences. In addition, the writer found 13 translation techniques used by KlikFilm subtitlers under the theory of Molina et al. (2002). The most dominantly used technique is established equivalent with a frequency of 87 data or 45.79% of the total data. Meanwhile, for the quality of imperative sentence translation in Spencer, the KlikFilm subtitle has good accuracy and high readability values, with 2.6 for accuracy and 2.9 for readability. This study shows that KlikFilm, an Indonesian local and legal streaming service, has good accuracy and high readability in producing a subtitle, particularly for an unreleased movie in Indonesian theatres or major streaming services such as Spencer.